Lipase B of Candida antarctica Co-adsorbed with Polyols onto TiO2 Nanoparticles for Improved Biocatalytic Performance - Llerena Suster, Carlos Rafael (2017)
BACKGROUND The immobilization of the lipase B of Candida antarctica CALB overTiO2 nanoparticles was thoroughly investigated with the isotherms of adsorption at various temperatures with and without the addition of sorbitol and glycerol. The surface composition, secondary structure and the effect of the addition of the polyols was addressed.RESULTS The maximum dispersion limit of protein on TiO2 NPs is 0.073 ± 0.007μmol. Glycerol and sorbitol co-adsorb on the TiO2 NPs reaching 45 % of thesurface composition of the biocatalyst. The optimized material was able to catalyze the esterification of 52 % of R/S-ibuprofen with ethanol (0.31 ± 0.01 μmol.min-1.mg-1) with 41 % of enantiomeric excess towards S(+)-ibuprofen in 24 hs of reaction. Under similar reaction conditions, the commercial counterpart Novozym® 435 showed 34 % of conversion (0.091 ± 0.003 μmol.min-1.mg-1) and 16 % of enantiomeric excess.CONCLUSIONS The molecular association between the protein and the polyolsexerts a positive cooperativism since prevents the aggregation of the protein and protects its active conformation. The residual esterase activity of the immobilized CALB compared with the free lipase depends directly on the amount of co-adsorbed polyols. Moreover, polyols boost the catalytic performance in the kinetic resolution of racemic ibuprofen showing an optimum at the maximum coverage of polyols on the biocatalysts.